2015
DOI: 10.1017/s1047951115000360
|View full text |Cite
|
Sign up to set email alerts
|

The role of curcumin as an inhibitor of oxidative stress caused by ischaemia re-perfusion injury in tetralogy of Fallot patients undergoing corrective surgery

Abstract: Cardioprotective effects of curcumin may include inhibition of the c-Jun N-terminal kinase pathway and caspase-3 in cardiomyocytes, particularly in the ischaemia phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A small study evaluated the effect of allopurinol supplementation in TOF surgery, showing less ROS expression in myocardial tissue, but no difference in MDA concentration in coronary sinus blood was observed [ 161 ]. Also, the use of curcumin, a potent ROS scavenger, in TOF surgery results in decreased c-Jun N-terminal kinase activity in cardiomyocyte nuclei and less caspase-3 expression, which relates to better right and left ventricle systolic function [ 162 ].…”
Section: Antioxidant-based Strategies In Congenital Heart Disease mentioning
confidence: 99%
“…A small study evaluated the effect of allopurinol supplementation in TOF surgery, showing less ROS expression in myocardial tissue, but no difference in MDA concentration in coronary sinus blood was observed [ 161 ]. Also, the use of curcumin, a potent ROS scavenger, in TOF surgery results in decreased c-Jun N-terminal kinase activity in cardiomyocyte nuclei and less caspase-3 expression, which relates to better right and left ventricle systolic function [ 162 ].…”
Section: Antioxidant-based Strategies In Congenital Heart Disease mentioning
confidence: 99%
“…1,2 A previous study demonstrated that CME-induced local myocardial inflammation is the central link leading to myocardial injury and progressive cardiac dysfunction subsequently. 10 The recent studies on cardiovascular diseases have shown that curcumin exerts multiple cardiovascular protective effects, such as antioxidative stress, 11 anti-inflammation, 12 antiapoptosis, 13 antiheart failure, 14 anticardiac hypertrophy, 15 and antiatherosclerosis. Some endogenous ligands led to the release of inflammatory factors, such as tumor necrosis factor α (TNF-α) and interleukin-1β (IL-1β), by activating the toll-like receptor 4 (TLR4) receptor and NF-κB.…”
Section: Introductionmentioning
confidence: 99%
“…Morover, Cu also has been reported to attenuate ischemia reperfusion injury by reducing ischemia reperfusion‐induced mitochondrial oxidative damage through the activation of SIRT1 signaling . Furthermore, Sukardi et al found that Cu could process the cardioprotective effects via the inhibition of the c‐Jun N‐terminal kinase pathway and caspase‐3 in cardiomyocytes, particularly in the ischemia phase . However, there is still no study on whether Cu is beneficial to diabetic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…22 Furthermore, Sukardi et al found that Cu could process the cardioprotective effects via the inhibition of the c-Jun Nterminal kinase pathway and caspase-3 in cardiomyocytes, particularly in the ischemia phase. 23 However, there is still no study on whether Cu is beneficial to diabetic cardiomyopathy. Therefore, our research aims to evaluate the effects of Cu on diabetic cardiomyopathy and explore its possible mechanism.…”
mentioning
confidence: 99%